Effects of music therapy and music-based interventions in the treatment of substance use disorders: A systematic review. - Louisa Hohmann; Joke Bradt; Thomas Stegemann; Stefan Koelsch (PLoS ONE)
Music therapy (MT) and music-based interventions (MBIs) are increasingly used for the treatment of substance use disorders (SUD). Previous reviews on the efficacy of MT emphasized the dearth of research evidence for this topic, although various positive effects were identified. Therefore, we conducted a systematic search on published articles examining effects of music, MT and MBIs and found 34 quantitative and six qualitative studies. There was a clear increase in the number of randomized controlled trials (RCTs) during the past few years. We had planned for a meta-analysis, but due to the diversity of the quantitative studies, effect sizes were not computed. Beneficial effects of MT/ MBI on emotional and motivational outcomes, participation, locus of control, and perceived helpfulness were reported, but results were inconsistent across studies. Furthermore, many RCTs focused on effects of single sessions. No published longitudinal trials could be found. The analysis of the qualitative studies revealed four themes: emotional expression, group interaction, development of skills, and improvement of quality of life. Considering these issues for quantitative research, there is a need to examine social and health variables in future studies. In conclusion, due to the heterogeneity of the studies, the efficacy of MT/ MBI in SUD treatment still remains unclear.